Multinational Construction Companies in Nigeria: An Analysis of their Impact on Economic Growth and Dependency - Tola Benjamin Kehinde; Busola Elizabeth Simon-Ilogho (International Journal of Economic, Finance and Business Statistics, 2023)
This paper examines the impact of multinational construction companies on Nigeria's economy, employing a descriptive research design and drawing on the framework of dependency theory. The study specifically focuses on the practices and effects of multinational construction companies operating within Nigeria. The findings from the research indicate a mixed impact of multinational construction companies on the Nigerian economy. On one hand, some multinational companies have been found to engage in exploitative practices, while other hand, there are instances where multinational construction companies have contributed positively to the Nigerian economy, through technological advancements, increased employment opportunities, and investments in local infrastructure development. Based on the study's findings, the paper recommends an increase in collaboration between local construction companies and multinational corporations. This collaboration can facilitate knowledge transfer, technology sharing, and capacity building within the Nigerian construction industry. Additionally, it emphasizes the importance of implementing robust regulations and policies to ensure responsible and sustainable practices by multinational construction companies operating in Nigeria. The paper spotlights the complex dynamics between multinational construction companies and Nigeria's economy, highlighting both negative and positive impacts. The paper underscores the significance of fostering collaboration and implementing effective regulatory frameworks to maximize the positive contributions of multinational construction companies while mitigating any adverse effects on Nigeria's economy.